2014
DOI: 10.4103/2141-9248.144896
|View full text |Cite
|
Sign up to set email alerts
|

Toothache and self-medication practices: A study of patients attending a niger delta tertiary hospital in nigeria

Abstract: Background:There is evidence that self-medication practices among dental patients with toothache are common, and despite the adverse clinical consequences, there is a paucity of literature on it, and only few programs are available for its control.Aim:The aim was to assess the self-medication practices among adult dental patients suffering from toothache.Subjects and Methods:An instrument adapted from modified form of 117-item self-report questionnaire based on world Health Organization guidelines for students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
32
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 20 publications
15
32
3
3
Order By: Relevance
“…Some of these studies revealed over-the-counter analgesics as the most commonly used compared with other remedies [4,11,7,12,13]. The results of this study showed that among different remedies used by the participants, cloves was the most frequently used remedy 33.8% along with herbal remedies 19.6% and OTC medications 19%.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Some of these studies revealed over-the-counter analgesics as the most commonly used compared with other remedies [4,11,7,12,13]. The results of this study showed that among different remedies used by the participants, cloves was the most frequently used remedy 33.8% along with herbal remedies 19.6% and OTC medications 19%.…”
Section: Discussionsupporting
confidence: 52%
“…The questionnaire consisted of objectivesoriented questions, some of which were also obtained from similar studies that conducted in other countries [4,11]. The questionnaire was prepared in English first and then translated into Arabic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the central premise of the current study that it is likely that the provision of vital information on the prevention of maternal mortality will lead to a significant drop in the rates seen in Nigeria (Igberase, Isah & Igbekoyi, 2009) Self-medication may be pervasive and even recommended for treatment of minor diseases, but due to the potential negative outcome of this practice (Befekadu, Dhekama, & Mohammed, 2014), it was suggested (Anyanechi & Saheeb, 2014) that the process be eradicated or reduced to the minimum through health education and enlightenment campaigns. Adeusi, Adekeye, & Ebere (2014) stressed the urgency in the appropriate health education of the women, to enable them make informed health decisions regarding their health and that of their children.…”
Section: Poor Awareness/lack Of Informationmentioning
confidence: 99%
“…Numerous studies have reported that self-medication is a common behavior in both developed and developing countries (7,8). For instance, in European countries, the frequency of selfmedication for general health issues was observed to be 68% -78% (9), while it was 80% -94.5% in Asian countries, such as Saudi Arabia, Kuwait, Pakistan, and Bahrain (10)(11)(12)(13), and 80% -100% in African countries such as Cameroon, Nigeria, and Egypt (14,15). Furthermore, the prevalence of self-medication in Iran is estimated to be three times the world average, with an estimate of 83.3% (16,17).…”
Section: Introductionmentioning
confidence: 99%